Comparative Law in Antebellum America - M.H. Hoeflich (Washington University Global Studies Law Review, 2005)
The Founding Fathers, their children, and their grandchildren found themselves living in a new nation where they were not just free to innovate legally, but obligated to do so. They had at their disposal, of course, the long English tradition of common law. They also had the system of Roman law, particularly the works of which they had some knowledge from their study of Latin literature, Cicero and Quintilian, new scholarship on both Roman law and modern civil law coming from Germany and France, as well as, basic knowledge of some exotic legal systems brought back by the British from their Asian empire. Finally, they had laws which they had created themselves in the thirteen colonies. At the time, lawyers, legislators, and judges also recognized the need to create a unique system of laws suitable for their new experiment in democracy. Virtually every new state passed legislation formally receiving the common law of England as it had existed prior to the Revolution, but each state refused to be bound by post-revolutionary statutes or decisions. Obviously, this generation of lawyers and judges had been trained in the English common law, and they were not going to abandon it completely. But, they faced the choice: whether to continue the English legal line or to strike out on a new path. Influential in their decision-making was a recognition that English cases and statutes suffered from several practical disabilities to implementation. First, the physical and financial context of English law was different from that of the new nation. The English common law developed in a context in which property was scarce and labor generally cheap. However, in the new American nation, property was cheap and plentiful but labor was often scarce. Second, the political wounds of the Revolution were slow to heal and were reopened by the War of 1812. Therefore, by the second decade of the nineteenth century, the English common law was widely seen as the legal system of a tyrannous enemy regime. Thus, in the early decades of our national history, there were reasons for American jurists to look seriously at other legal systems as well as a number of other legal systems at which to look. We may categorize antebellum jurists as falling within three groups: (1) those who favored a wholesale abandonment of the common law and its replacement by a new, uniquely American system, based perhaps on Roman or European models; (2) those who favored giving priority to the common law system, while recognizing that English precedents and statutes would, of necessity, often need to be replaced; and (3) a few hardy souls who sought to maintain, as much as possible, the common law tradition. It is the members of these first two groups, whom we may label as “proto-comparativists,” who most interest us today.
Keywords: Antebellum period; 1820-1861; Comparative law; United States